Definitions of frontal bone inclination: Applicability and quantification. (October 2019) - Koelzer, Sarah C.; Kuemmel, Ines V.; Koelzer, Jan T.; Ramsthaler, Frank; Holz, Franziska; Gehl, Axel; Verhoff, Marcel A.
Highlights: 10 definitions of frontal bone inclination were tested for sex discrimination. Application-specific software has been developed for this research project. Statistically significant sex differences have been found for 4 of the definitions. One definition can be recommended with regard to inter- and intra-rater reliability. Abstract: In sex determination from crania, a "vertical" forehead is considered a female feature, while a "sloping" forehead is considered a male feature. Precise description of frontal inclination with a quantitative measure like an angle is considerably more difficult as it requires accurate identification of clearly defined craniometric points. In the literature, the morphognostic terms "frontal bone inclination, " or "frontal profile, " are defined in numerous ways. The aim of this study was to determine which of these frontal inclination definitions is best suited for sex estimation. In a study in the context of the digital forensic osteology project, 10 of the frontal angle definitions described in the literature were assessed for their usefulness in sex determination on 211 virtual crania, reconstructed from postmortem CT-data. Custom-developed software was used for the automated measurement of frontal bone inclination angles from lateral-profile, volume-rendered 3D cranial images in which 10 anthropometric landmarks had been manually marked. Discriminant function analysis was performed to determine if satisfactory accuracy rates for the classification of sex could be achieved with defined variables. Four of the ten examined definitions were found to be highly significant for sex determination; three of these, also provided satisfactory intra- and inter-observer reliability. The frontal angle according to Schwalbe provided the best accuracy rate of 75.4% and a critical discriminatory value (separation value) of 88.6°: angles greater than this, suggest female sex; angles smaller than this, suggest male sex. Further, the open-source, custom-developed software introduced here proved compatible with commonly used image-processing and statistical programs and allowed quick, automated, valid measurement of numerous cranial angles. Other craniometric angles can, thus, also be quickly and easily determined with this software.